2015
DOI: 10.7906/indecs.13.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Agent Based Framework for Modelling Smart Self-Sustainable Systems

Abstract: Self-sustainability is a property of a system; a system is considered to be self-sustainable if it can sustain itself without external support in an observed period of time. If this property is mapped to a human settlement in context of resources (water, energy, food, etc.), it would describe a human settlement which is independent of external resources (like the national electrical grid or a central water distribution system), where such external resources are either not available, or not desirable.This artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Self-sustainability as defined in this paper has only recently induced explicit research efforts in forms of modelling and simulations of human settlements which directly facilitate such property [Tomičić and Schatten, 2015, Tomičić and Schatten, 2016, Tomicic and Schatten, 2016. Authors have demonstrated that a software framework based on the multi-agent modelling paradigm has the ability to model and simulate selfsustainable human settlements, and the ability to prolong the self-sustainability period of such settlements by using dedicated mechanisms working together across multiple dwelling units, sharing a common top-level goal [Tomičić and Schatten, 2016].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-sustainability as defined in this paper has only recently induced explicit research efforts in forms of modelling and simulations of human settlements which directly facilitate such property [Tomičić and Schatten, 2015, Tomičić and Schatten, 2016, Tomicic and Schatten, 2016. Authors have demonstrated that a software framework based on the multi-agent modelling paradigm has the ability to model and simulate selfsustainable human settlements, and the ability to prolong the self-sustainability period of such settlements by using dedicated mechanisms working together across multiple dwelling units, sharing a common top-level goal [Tomičić and Schatten, 2016].…”
Section: Related Workmentioning
confidence: 99%
“…where A stands for photovoltaic system-to-load, B for storage-to-load, and C for gridto-load [e Silva and Hendrick, 2016]. In complement to the self-sustainability described by authors in [Tomičić and Schatten, 2015, Tomičić and Schatten, 2016, Tomicic and Schatten, 2016, where the self-sustainability is modeled as a binary property, the presented formula clearly illustrates the degree to which the system is self-sustainable in respect to the resources used from outside the system itself.…”
Section: Related Workmentioning
confidence: 99%